What Was Artificial Intelligence? - Curry Jansen, Sue (mediastudies.press, 2022)
When it was originally published in 2002, Sue Curry Jansen’s “What Was Artificial Intelligence?” attracted little notice. The long essay was published as a chapter in Jansen’s Critical Communication Theory, a book whose wisdom and erudition failed to register across the many fields it addressed. One explanation for the neglect, ironic and telling, is that Jansen’s sheer scope as an intellectual had few competent readers in the communication studies discipline into which she published the book. “What Was Artificial Intelligence?” was buried treasure. In this mediastudies.press edition, Jansen’s prescient autopsy of AI self-selling—the rhetoric of the masculinist sublime—is reprinted with a new introduction. Now an open access book, “What Was Artificial Intelligence?” is a message in a bottle, addressed to Musk, Bezos, and the latest generation of AI myth-makers.